LEARNING MANAGEMENT IN THE PANDEMIC - Rajab, Shiddiqi; Mahmudah, Fitri Nur; Damayanti, Deasy Lisa (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The COVID-19 outbreak to date has had a significant impact on the world of education, so the majority of schools in Indonesia are still using online learning systems. The implications of several policies that have been set by the government regarding the learning system during the pandemic, require schools to support online learning. Based on these problems, this study was made to determine learning management during the pandemic. This research is a type of qualitative research using the descriptive method in which the search for source information and data collection is done by interview and documentation method. Based on interviews conducted with several teachers of SMAS Muhammadiyah Tanjung Redeb, it can be concluded that in the learning process, the use of the right method is a must or an absolute thing that must be done in order to achieve learning objectives. Meanwhile, online learning can be done through various learning applications. The use of the correct method combined with the right strategy will make the learning implementation strategy work as expected. In addition, obstacles in learning occur if there are obstacles to the learning process, especially from human factors (teachers and students), institutional factors (classrooms), and educational factors (lack of teaching materials). Furthermore, the measure of the success of the learning process is through effective learning, which includes several factors such as available media resources, high learning motivation, student activities, smooth network access, task results, sufficient materials, and supportive locations.